Pencegahan Gangguan Kesehatan Jiwa pada Remaja di Masa Pandemi Covid-19 dengan Perilaku “CERDIK CERIA” - Leliana Wuarlela; Lusa Rochmawati (Jurnal Indonesia Sehat, 2022)
Background: People are not ready to face the COVID-19 pandemic, physically or psychologically. Teenagers who often do activities outside the home such as going to school, playing, and others are affected. Behavioral factors (behavior causes) and factors outside of behavior (non-behavior causes) affect the health of a person or society. Efforts to overcome mental health in adolescents with "CERDIK CERIA" behavior. Aims: To determine the prevention of mental health in adolescents during the covid-19 pandemic with the behavior of "CERDIK CERIA". Methods: Analytical survey research with a cross sectional approach, with a sample of some students of STIKes Yogyakarta in the 2021/2022 academic year as many as 57 respondents. The research instrument used a questionnaire. Aspects that are assessed as "CERDIK CERIA" behavior are based on predisposing, enabling and reinforcing factors. Analysis of the data using univariate analysis is presented in the form of a percentage of the frequency distribution table. Results: Prevention of mental health in adolescents during the COVID-19 pandemic with "CERDIK CERIA" behavior at STIKes Yogyakarta was generally in the good category as many as 26 respondents (45.6%). Mental health behavior in adolescents during the covid-19 pandemic with "CERDIK CERIA" behavior based on predisposing factors in the good category as many as 36 respondents (63.2%); based on enabling factors in the good category as many as 29 respondents (50.3%); and based on reinforcing factors in the good category as many as 26 respondents (45.6%). Conclusion: In general, the prevention of mental health in adolescents during the COVID-19 pandemic with the "CERDIK CERIA" behavior at STIKes Yogyakarta is in the good category.